First report of Colletotrichum siamense causing grape ripe rot in Brazil - Batista, Diógenes da Cruz; Vieira, Willie Anderson Santos; Barbosa, Maria Angélica; Camara, Marcos Paz Saraiva (Plant disease, 2023)
cv. BRS Vitória is a seedless black table grape cultivar with an extremely pleasant flavor and is adapted to cultivation in all Brazilian regions. Between November and December 2021, grape berries presenting typical ripe rot symptoms were found in three vineyards located in Petrolina, Pernambuco Brazil. The first symptoms are small and depressed lesions on ripe berries, presenting tiny black acervuli. As the disease progress, lesions enlarge and affect the whole fruit, and abundant orange masses of conidia can be observed. Finally, berries become completely mummified. Symptoms were observed in the three vineyards visited, and disease incidence was above 90%. Some producers are considering eradicating the plantations due to the losses caused by the disease. Control measures used so far are costly and ineffective. Fungal isolation was performed by transferring conidial masses from 10 diseased fruit to plates containing potato dextrose agar medium. Cultures were incubated at 25 °C under continuous light. Seven days after inoculation, three fungal isolates (LM1543-1545) were obtained and subcultivated in pure culture for species identification and pathogenicity test. Isolates presented white to grey cottony mycelia, and hyaline conidia with cylindrical with rounded ends, which resemble the genus (Sutton 1980). Partial sequences of APN2-MAT/IGS, CAL, and GAPDH loci were amplified, sequenced, and deposited on GenBank (OP643865-OP643872). Isolates from were placed within the clade including the ex-type and representative isolates of . The clade was strongly supported (99.8% bootstrap support) in the maximum likelihood multilocus tree of the three loci combined, which confidently assign the isolates to this species. Inoculation on grape bunches was performed to confirm pathogenicity. Grape bunches were surface sterilized for 30 s in 70% ethanol, 1 min in 1.5% NaOCl, rinsed two times with sterile distilled water, and air-dried. Fungal conidial suspensions (10 conidia mL ) were sprayed to the point of run-off. The negative control was represented by grape bunches sprayed with sterile distilled water. Grape bunches were kept in a humid chamber for 48 h at 25 °C and a light period of 12 h. The experiment was conducted with four replicates (four inoculated bunches per isolate) and repeated once. Typical ripe rot symptoms were observed on grape berries 7 days after inoculation. No symptoms were observed on the negative control. The fungal isolates recovered from inoculated berries were morphologically identical to the isolates originally recovered from symptomatic berries collected in the field, fulfilling Koch's postulates. was reported in association with grape leaves in USA (Weir et al. 2012) and causing grape ripe rot in North America (Cosseboom & Hu 2022). Only , , , , and were reported causing grape ripe rot in Brazil (Echeverrigaray et al. 2020). To our knowledge, this is the first report of causing grape ripe rot in Brazil. This finding is important for disease management because has a high phytopathogenic potential due to its wide distribution and host range.